1994
DOI: 10.1007/bf00865405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of posture, hypotension and locally applied vasoconstriction on the middle ear microcirculation in anaesthetized humans

Abstract: Studies by laser-Doppler flowmetry of middle ear microcirculation changes induced by physical and chemical stimuli in the animal have only recently been made. This prospective study, performed in humans, was designed to compare the effects of a postural manoeuvre (headup tilt 30 degrees), hypotension and locally applied vasoconstriction on middle ear blood flow during anaesthesia. Circulatory changes provoked by a headup tilt of 30 degrees, and successive intravenous boluses of potent vasodilators, were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 30 publications
0
25
1
Order By: Relevance
“…4 The optic fibre is inserted through the tympanic perforation and is put in place by the surgeon on the mucosa of the promontory of the tympanic cavity. The MEBF was calibrated before the study so that a true zero indicated that the flux was null: MEBF and arterial blood pressure were continuously and simultaneously recorded.…”
Section: Middle Ear Blood Flow Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…4 The optic fibre is inserted through the tympanic perforation and is put in place by the surgeon on the mucosa of the promontory of the tympanic cavity. The MEBF was calibrated before the study so that a true zero indicated that the flux was null: MEBF and arterial blood pressure were continuously and simultaneously recorded.…”
Section: Middle Ear Blood Flow Changesmentioning
confidence: 99%
“…The MEBF was calibrated before the study so that a true zero indicated that the flux was null: MEBF and arterial blood pressure were continuously and simultaneously recorded. 4 The relative changes in MEBF (*MEBF) and in SABP from their respective baselines C were considered for statistical analysis and comparison between groups. The MEBF autoregulatory responses to controlled hypotension were quantified by the closed-loop gain factor of autoregulation (Ga) calculated from the equation Ga= 1-(%MEBF/ %MABP).…”
Section: Middle Ear Blood Flow Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Beta blockers decrease CO and therefore decrease the blood flow to the tissue. So, beta blocker would be appropriate for decreasing the bleeding which result from capillary injury [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that betablockers are responsible for improvement of the cardiovascular condition and patients' hemodynamic stability via changes in stress related physiological response (5,8). For this purpose we studied the effect of beta-blockers and the patient's position on the surgical table to induce hypotension (9,10). A number of different beta-blockers at different doses have already been tested, but we chose an easily obtained drug, oral metoprolol for this study.…”
Section: Patients and Methods: In A Randomized Controlled Open Clinmentioning
confidence: 99%